Pengaruh DAR, Ukuran Perusahaan, Risiko, Pajak, dan Likuiditas terhadap Profitabilitas Perusahaan Sektor Pertambangan di Indonesia - Robi Pramana Kusuma (Universitas Negeri Surabaya, 2018)
The purpose of this research was to understand the influence of DAR (Debt to Asset Ratio) , size, risk, tax, and liquidity on profitability (Return On Asset Ratio). This research is classified under a casual research and using purposive sampling method, thus 27 companies have been acquired that meet the criteria. A data analysis technique was used multiple linier regression analysis. The object of this study were listed mining sector company of Indonesia Stock Exchange period 2011 2015. The data is documented from company financial and annual report. The methods of data analysis were multiple regression model. The result of this study indicates that DAR, risk, tax, and liquidity has no influence on companys profitability. Meanwhile, size of the company has a positive influence on companys profitability that represented by return on asset ratio.